Personal Rituals in Adolescence: Their Role in Emotion Regulation and Identity Formation - Demmrich, Sarah (Journal of empirical theology, 2018)
This study examines the meaning of personal rituals for the adolescent identity development and emotion regulation. Both are ritual functions and can be characterized as adolescent developmental tasks. However, there is no consistent pattern in previous research to explain the processes for how identity is formed and emotions are regulated during the performance of personal rituals. Therefore, a questionnaire study among 410 (182 male) adolescents (age: M = 15.06, SD = .61) was carried out. The questionnaire used the Berzonsky Identity Style Inventory and various measures to assess different experiences during the ritual (i.e. mood, emotion regulation, reality-transforming experiences). After separating spiritual from non-spiritual rituals, the results showed that spiritual rituals were used as a means for emotion regulation. Furthermore, self-reflection was closely related to the information-oriented identity style. The findings are discussed against the background of the impact of spiritual practices for emotional and identity development in adolescence.